Inferring the Effects of Compositional Boundary Layers on Crystal Nucleation, Growth Textures, and Mineral Chemistry in Natural Volcanic Tephras through Submicron-Resolution Imaging - Zellmer, Georg F.; Sakamoto, Naoya; Hwang, Shyh-Lung; Matsuda, Nozomi; Iizuka, Yoshiyuki; Moebis, Anja; Yurimoto, Hisayoshi (Frontiers in Earth Science, 2016)
Crystal nucleation and growth are first order processes captured in volcanic rocks and record important information about the rates of magmatic processes and chemical evolution of magmas during their ascent and eruption. We have studied glass-rich andesitic tephras from the Central Plateau of the Southern Taupo Volcanic Zone by electron- and ion-microbeam imaging techniques to investigate down to sub-micrometre scale the potential effects of compositional boundary layers (CBLs) of melt around crystals on the nucleation and growth of mineral phases and the chemistry of crystal growth zones. We find that CBLs may influence the types of mineral phases nucleating and growing, and growth textures such as the development of swallowtails. The chemistry of the CBLs also has the capacity to trigger intermittent overgrowths of nanometre-scale bands of different phases in rapidly growing crystals, resulting in what we refer to as cryptic phase zoning. The existence of cryptic phase zoning has implications for the interpretation of microprobe compositional data, and the resulting inferences made on the conditions of magmatic evolution. Identification of cryptic phase zoning may in future lead to more accurate thermobarometric estimates and thus geospeedometric constraints. In future, a more quantitative characterization of CBL formation and its effects on crystal nucleation and growth may contribute to a better understanding of melt rheology and magma ascent processes at the onset of explosive volcanic eruptions, and will likely be of benefit to hazard mitigation efforts.